The transcultural Ottoman table. (October 2019) - Roden, Claudia
Claudia Roden writes about the Egypt she grew up in – a mixed cosmopolitan world with long-established communities of Armenians, Greeks, Italians, Syrians and Lebanese, as well as French and British expatriates. Roden was born in Cairo in the Jewish community that was itself a mosaic of people who had come from all over the Ottoman Empire. Roden recounts her experiences of collecting recipes from communities who were leaving Egypt after the Suez crisis in 1956 and her nostalgia and determination to preserve a culture that disappeared, and which had few written recipes. This led her to research the cooking of Middle Eastern countries and becoming interested in the cultural and historical background of the food. She focuses on the sophisticated cuisine that developed in ex-Ottoman countries, and Lebanon in particular, emphasizing the importance of transcultural exchanges and memories around the table.